Implementation of Core Values of SOEs "Akhlak" Maqasid Al-Shari'ah Perspective to Improve Legal Compliance - Apriadi, Didi; Sugianto, Sugianto (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
The corporate culture of SOEs is known as core values that are set as the identity and glue of work culture supported by continuous performance improvement. Core values are principles and values that become the foundation and reference of a company. Core values in SOEs are known as "AKHLAK" which is also a moral guideline in facing various shocks in the VUCA era (Volatility, Uncertainty, Complexity, Ambiguity). With the theory of maqashid shari'ah is an important concept in the discussion of Islam to realize the benefit of mankind. However, it contributes to making the concept of maqashid shari'ah more applicable and functional for Islamic law in dealing with affairs in the contemporary context, especially in muamalah and worship. This is very important for companies because various problems must be faced by SOEs, namely moral values that are not upheld, so with "AKHLAK" as a moral value that will bring SOEs and individuals in them to progress and contribute to the country